Pengukuran Kualitas Pelayanan Angkutan Kota Melalui Kinerja Terhadap Kepuasan Masyarakat di Kota Malang - Blima Oktaviastuti; Rifky Aldila Primasworo; Pamela Dinar Rahma; M. Sa'dillah; Helena N. Mini (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2022)
The transportation aspect is the most dominant sector in making it easier for humans to move places. Like supply and demand, the wheels of frugality cannot be separated from the contribution of transportation. The development of the times has made land transportation increasingly provide public transportation options. Online and conventional transportation compete for passengers, one of which is city transport. This study aims to determine the performance of city transportation on the Arjosari-Mergan-Gadang (AMG) route. The research design used is quantitative using descriptive and survey types. The study was conducted by calculating the number of passengers and AMG public transportation operating on weekdays and weekends. The calculation is carried out by observing at a predetermined location point and participating in becoming an AMG angkot passenger. The data used in this study is of two types, namely primary data and secondary data. Based on the results of the study, it was obtained that the assessment of the performance of AMG route city transportation is classified as a good category. The details of the AMG route assessment include headway, passenger waiting time, frequency, travel time, and load factor on public transportation passenger routes AMG including good categories according to assessment standards. As for the parameters of the number of vehicles operating, service time, travel speed, start and end of service time are included in the category of less. Evaluation and improvement need to be carried out, because if an assessment is carried out per sub-variable, there is still a lack of assessment.